CONSUMER INTENTION TO USE ELECTRIC TAXI SERVICES IN INDONESIA: A TAM-TPB STUDY OF GREEN SM WITH TRUST AND ENVIRONMENTAL CONCERN - Ricky Halomoan Tampubolon; Novika Candra Astuti (CV. Radja Publika, 2026)
Electrifying app-based mobility services has become a practical route to lower-carbon urban transport in emerging markets. How consumers actually decide to use such services, however, remains under-researched. This study investigates the constructs that shape consumer Intention to use Green SM, Indonesia's first all-electric taxi operator. The analytical framework integrates the Technology Acceptance Model and the Theory of Planned Behavior, extended with Trust and Environmental Concern. Data came from 240 active ride-hailing users in Greater Jakarta, analyzed using Partial Least Squares Structural Equation Modeling with 5,000 bootstrap resamples. Of seven hypotheses tested, four received support. Trust emerged as the strongest predictor of Attitude (β = 0.413, f² = 0.224), a pattern that cuts against the usual Perceived Ease of Use and Perceived Usefulness dominance in standard TAM applications. Attitude was the strongest predictor of Behavioral Intention (β = 0.505, f² = 0.297), with mediation analysis confirming Attitude as the central pathway through which Trust and Perceived Usefulness translate into Behavioral Intention. The model accounted for 52.8% of variance in Attitude and 46.6% in Behavioral Intention. The findings yield a transferable proposition for emerging markets: provider credibility is the primary lever for converting consumers, not feature parity or environmental appeal.